Aplikasi Mulsa Alang-Alang (Imperata cylindrica) dan Pengolahan Tanah terhadap Pertumbuhan Gulma di Areal Perkebunan Kelapa Sawit - Vira Irma Sari (JURNAL CITRA WIDYA EDUKASI, 2019)
Imperata cylindrica is belongs to the class A weed group (very dangerous). Control of weeds regularly continues, and this causes high weed waste in plantations. One of the activities carried out to handle it is to use it as mulch to maintain moisture and reduce weed growth. Mulch application will be more optimal if combined with tillage, because weed seeds in the soil will be cut off and fail to germinate. The combination of these two activities is expected to be able to control the growth of weeds and maintain good soil conditions. This study aims to obtain alternative pre-growing weed control, determine the effectiveness of mulch application and soil management activities in controlling weeds. This research was conducted in Experimental Garden 2 and Biology Laboratory of Polytechnic Kelapa Sawit Citra Widya Edukasi Bekasi, from April to May 2017. The research was arranged in a Factorial Randomized Block Design (RBD), the first factor was the application of mulch consisting and the second factor is tillage The results of the experiment showed that the application of mulch Imperata cylindrica and tillage can be used as an alternative activity to control weeds and the real interaction between the two activities can be seen in the number of weeds 1 Week After Planting (1 WAP). Mulch application has a single significant effect on the number of weeds 2 and 3 WAP, whereas tillage does not show any significant effect on all parameters.